Project Complexity Indicators and Management Strategies – A Delphi Study. (2016) - Kermanshachi, Sharareh; Dao, Bac; Shane, Jennifer; Anderson, Stuart
Abstract: Construction industry experts believe that project performance frequently suffers due to construction complexity issues. However, there are limited studies focusing on construction project complexity definition, characteristics and indicators. In this paper, a qualitative Delphi method was applied to identify and validate significant complexity indicators. To fulfill this purpose, ten Subject Matter Experts (SMEs) were invited to participate in a complexity assessment and management workshop. Through two rounds of the Delphi study, the top 30 complexity indicators were identified and ranked. It was concluded that "peak number of participants on the Project Management Team during engineering/design phase of the project", "magnitude of change orders impacting project execution", and "frequency of the workarounds" are the top three complexity indicators respectively. Furthermore, the impact weight associated with each of the complexity indicators were calculated. In the second part of the workshop, the Delphi methodology was again utilized to capture complexity management strategies and practices.